Metabolic Response of Pakchoi Leaves to Amino Acid Nitrogen - Xiao-li WANG; Wen-juan YU; Qian ZHOU; Rui-feng HAN; Dan-feng HUANG (Journal of Integrative Agriculture, 2014)
Different nitrogen (N) forms may cause changes in the metabolic profiles of plants. However, few studies have been conducted on the effects of amino acid-N on plant metabolic profiles. The main objective of this study was to identify primary metabolites associated with amino acid-N (Gly, Gln and Ala) through metabolic profile analysis using gas chromatography-mass spectrometry (GC-MS). Plants of pakchoi (Brassica campestris L. ssp. chinensis L.), Huawang and Wuyueman cultivars, were grown with different nitrogen forms (i.e., Gly, Gln, Ala, NO3−-N, and N starvation) applied under sterile hydroponic conditions. The fresh weight and plant N accumulation of Huawang were greater than those of Wuyueman, which indicates that the former exhibited better N-use efficiency than the latter. The physiological performances of the applied N forms were generally in the order of NO3−-N>Gln>Gly>Ala. The metabolic analysis of leaf polar extracts revealed 30 amino acid N-responsive metabolites in the two pakchoi cultivars, mainly consisting of sugars, amino acids, and organic acids. Changes in the carbon metabolism of pakchoi leaves under amino acid treatments occurred via the accumulation of fructose, glucose, xylose, and arabinose. Disruption of amino acid metabolism resulted in accumulation of endogenous Gly in Gly treatment, Pro in Ala treatment, and Asn in three amino acid (Gly, Gln and Ala) treatments. By contrast, the levels of endogenous Gln and Leu decreased. However, this reduction varied among cultivars and amino acid types. Amino acid-N supply also affected the citric acid cycle, namely, the second stage of respiration, where leaves in Gly, Gln and Ala treatments contained low levels of malic, citric and succinic acids compared with leaves in NO3−-N treatments. No significant difference in the metabolic responses was observed between the two cultivars which differed in their capability to use N. The response of primary metabolites in pakchoi leaves to amino acid-N supply may serve an important function in pakchoi adaptation to amino acid-N sources.